2017
DOI: 10.1002/anie.201700713
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Gene Transfection through Inhibition of β‐Sheet (Amyloid Fiber) Formation of a Short Amphiphilic Peptide by Gold Nanoparticles

Abstract: The effect of citrate-stabilized gold nanoparticles (AuNPs) on the secondary structure of an artificial β-sheet-forming cationic peptide has been studied. The AuNPs inhibited β-sheet formation and led to fragmented fibrils and spherical oligomers with assembled AuNPs on their surface. Besides this structural change, the functional properties of the peptide are also different. Whereas the peptide was unable to act as a vector for gene delivery, formation of a complex with AuNPs allowed successful gene delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…In 2017 the Schmuck group showed, that a β‐sheet forming peptide containing three GCP units ( T ‐ 6 ) (Figure ), acts as an efficient transfection vector. This compound was found to form long fibrillar aggregates as proven by AFM and TEM measurements . These long fibres were unable to transfect cells even though it was shown that plasmid DNA was bound weakly to the fibres.…”
Section: Biomedical Applicationsmentioning
confidence: 92%
“…In 2017 the Schmuck group showed, that a β‐sheet forming peptide containing three GCP units ( T ‐ 6 ) (Figure ), acts as an efficient transfection vector. This compound was found to form long fibrillar aggregates as proven by AFM and TEM measurements . These long fibres were unable to transfect cells even though it was shown that plasmid DNA was bound weakly to the fibres.…”
Section: Biomedical Applicationsmentioning
confidence: 92%
“…Cyclic peptides of alternating chirality 102 incorporating guanidiniocarbonylpyrrole can self-assemble into fibers that can also be applied in plasmid transfection 100 . Alternation of guanidiniocarbonylpyrrole and cyclohexylalanine afforded large amyloid peptide fibers that can be further processed with gold nanoparticles to obtain nanoparticles of the right size for cell transfection 103 .…”
Section: Peptidesmentioning
confidence: 99%
“…Significant inhibition of DNA transfection by bafilomycin (a macrolide antibiotic that can block the endosomal acidification process) was observed, which further supports the endosomal uptake mechanism. Except for this small peptide, GCP was also integrated into larger peptides, including branched [29], three-armed [30,31], dendritic [32], and self-assembled oligomers [33,34] for gene delivery and transfection based on the endosomal uptake and release.…”
Section: Introductionmentioning
confidence: 99%